2021
DOI: 10.1002/gcc.22938
|View full text |Cite
|
Sign up to set email alerts
|

Unbalanced translocation der(5;17) resulting in a TP53 loss as recurrent aberration in myelodysplastic syndrome and acute myeloid leukemia with complex karyotype

Abstract: A complex karyotype, detected in myelodysplastic syndrome (MDS) and acute myeloid leukaemia (AML), is associated with a reduced median survival. The most frequent chromosomal aberrations in complex karyotypes are deletions of 5q and 17p harboring the tumor suppressor gene TP53. The unbalanced translocation der(5;17) involving chromosome 5q and 17p is a recurrent aberration in MDS/AML, resulting in TP53 loss. We analyzed the karyotypes of 178 patients with an unbalanced translocation der(5;17) using fluorescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
(38 reference statements)
0
1
1
Order By: Relevance
“…In this study, 6 patients were identified with this mutation, but it did not show a significant trend in the evaluation of AML disease in this study. In other studies, it has been shown that the presence of this mutation and its evaluation in relation to AML disease reduces the survival of patients and interferes in the care and treatment of patients, which is not in line with the results of the present study [18,19] .…”
Section: Factors Affecting Aml Mutations (Changes) In Genecontrasting
confidence: 89%
“…In this study, 6 patients were identified with this mutation, but it did not show a significant trend in the evaluation of AML disease in this study. In other studies, it has been shown that the presence of this mutation and its evaluation in relation to AML disease reduces the survival of patients and interferes in the care and treatment of patients, which is not in line with the results of the present study [18,19] .…”
Section: Factors Affecting Aml Mutations (Changes) In Genecontrasting
confidence: 89%
“…Unbalanced translocation der (5; 17) resulting in a TP53 loss [14], whole-arm translocation of der (5; 17) (p10; q10) with concurrent TP53 mutations [15] and reccuring abnormality dic (5; 17) associated also with mutations of TP53 [16] were described in AML. The association with P53 abnormalities was not tested in our patient.…”
Section: Discussionmentioning
confidence: 99%